The effects of physical activity on the prevention of mental illness in college students - Chaohu He; Liaokun Ye; Zhenpeng Huang , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
College students are the driving force behind national and social progress. They frequently face a great deal of mental and psychological pressure. If the pressure is not relieved promptly, it will significantly impact their mental health. This study aims to examine the preventative effect of sports training on the mental health diseases of college students. In China, mental health issues are receiving increasing attention and psychological pressure. The students were screened using the SCL-90 psychological test, and those without significant psychological illness were chosen as research participants. Before and after the experiment, the Simple mood State Scale (POMS) was measured twice; the influence of different sports on the mood state of college students is the subject of this study. The experiment was conducted on 200 Chinese college students. None of the students was afflicted with any unusual diseases. The invalid questionnaire and students who interrupted the experiment due to exceptional circumstances were disqualified. The final subjects of the experiment were 194 first-year students. This paper investigates the relationship between college students' participation in sports and their mental health status. Before and after the comparison, there is a significant difference (P 0.05), as determined by the difference test. It has been found that college students who frequently participate in sports have significantly better mental health than those who do not. They have high self-awareness and are effective at eliminating negative emotions such as anxiety and depression. Exercising is a method of proving their worth. Through psychological transfer, students can use psychological hints to motivate themselves to achieve their goals, thereby enhancing their self-confidence in other endeavours. Enhancing self-confidence will play a significant role in promoting the study, work, and life of college students. Oxygen plays an important role in cultivating students' mental health. It can help students establish mental health consciousness, enhance the ability of psychological adjustment, cultivate students' correct understanding of self, boost self-confidence, develop optimistic psychological qualities, enhance the ability to deal with setbacks and adapt to society, and promote the sound development of students' psychological health.